Comparing the minimal costs of Arctic container shipping between China and Europe: A network schemes perspective. (September 2021) - Liu, ChengCheng; Lian, Feng; Yang, Zhongzhen
Highlights: Perspective of Arctic shipping for container liner is illustrated. Shipping operating behaviors of liner shipping companies are considered. Feasibility Arctic container shipping is studies for a long term (20–30 years). Hub-Spoke network design model is built for the calculation. Abstract: To optimize the container liner shipping scheme between China and Europe as the possibility of Arctic shipping opens up, the operational behaviors of liner shipping companies are considered and potential shipping scheme are proposed. Fulfilling known port container OD flows, a model is built to optimize the liner shipping network corresponding to each proposed shipping scheme, where a single fleet or two fleets pass the Arctic or the Suez Canal. The profits of the liner company in the next 20 years under different schemes are compared. It is found that it is uneconomic to sail the Arctic for liner shipping between China and Europe and the Suez Canal Route is a better choice at present and far into the future.